What a Difference... The Royal Ballet's Sylvia - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2006)
A second look at the revival of Frederick Ashton's Sylvia. The dancers look far more comfortable in their roles, and it's vary good to see how their interpretations have changed and grown. PALABRAS CLAVE: Frederick Ashton, Sylvia, Royal Ballet, Darcey Bussell.